EL ESTILO LITERARIO EN LA EPOCA BARROCA - ABDULRAZZAQ AL-RUBAIEE, AHMED (Al-Adab Journal, 2018)
At the end of the middle eras, began in Spain an era of literary integration called it the (Golden era) Unlike political events which was prevalent there, Spain was from the side political lives he situation is stressed and internal divisions, but from the literary side She reached the peak of her relationship. The term Baroque refers to a movement of art, literature and culture, spread in Spain since the end of the sixteenth century until the end of the seventeenth century, In the seventeenth century began Literary productions from theater, novel, poetry and prose reach its grandeur, and there appeared prominent writers They knew in Spain and the world as well such as (Luba de Veca) and his style in theater and literary currents, Who followed his approach.The current study consists of two chapters:Chapter one refers to the beginning and prosperity and the end of baroque style in Spanish literature.The second chapter explains it operation evolution of the method (baroque) especially in lyric poetry of the baroque, We spoke in it about the most prominent figures in the field of poetry during the golden era.